Subjective Importance of a Common Feature Decides Its Consideration in Multi-attribute Decision-making - Wang, Ziyi; He, Guibing (Frontiers in Psychology, 2021)
One of the interesting research questions in multi-attribute decision-making is what affects the consideration of shared information (i.e., common features) between two alternatives. Previous studies have suggested two approaches (bottom-up and top-down) in finding what characteristics of common features affect their consideration. Two bottom-up factors (salience and interdependence) were found, but no top-down factors were discovered. In the current study, we followed the top-down approach and investigated how subjective importance of a common feature affects its consideration. In two studies, we consistently found that, on both the general and individual level, the level of consideration increased with the subjective importance of the common feature. This result provided a new explanation for the effect of common feature consideration and its individual difference, It also provided insights in explaining the underlying process of multi-attribute decision making.